2021
DOI: 10.1093/nargab/lqab118
|View full text |Cite
|
Sign up to set email alerts
|

Differential analysis of binarized single-cell RNA sequencing data captures biological variation

Abstract: Single-cell RNA sequencing data is characterized by a large number of zero counts, yet there is growing evidence that these zeros reflect biological variation rather than technical artifacts. We propose to use binarized expression profiles to identify the effects of biological variation in single-cell RNA sequencing data. Using 16 publicly available and simulated datasets, we show that a binarized representation of single-cell expression data accurately represents biological variation and reveals the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…An alternative approach such as comparing the proportion of expression across groups could be employed. Although it is beyond the scope of this discussion, there are methods that attempt to perform this type of proportional zero binary expression analysis [ 44 ]. Special attention should be paid to the identities of genes that fall into this category when considering DEG results as their results may be unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach such as comparing the proportion of expression across groups could be employed. Although it is beyond the scope of this discussion, there are methods that attempt to perform this type of proportional zero binary expression analysis [ 44 ]. Special attention should be paid to the identities of genes that fall into this category when considering DEG results as their results may be unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach such as comparing the proportion of expression across groups could be employed. Although beyond the scope of this discussion, there are methods that attempt to perform this type of proportional zero binary expression analysis [44]. Special attention should be paid to the identities of genes that fall into this category when considering DEG results as their results may be unreliable.…”
Section: Discussionmentioning
confidence: 99%
“… Qiu (2020) found that “dropout pattern in scRNA-seq data is as informative as the quantitative expression of highly variable genes” and suggested “embracing” dropout by using binarized data rather than transcript counts instead of ignoring it. Bouland et al (2021) found that a similar approach did indeed capture biologically meaningful variation in single cell transcriptomes. Nevertheless ( Jiang et al, 2022 ), criticized methods that use binarized gene expression data, because they ignore information from differential expression of the same genes in different cell types.…”
Section: Categories States and Semaphorantsmentioning
confidence: 96%